Internight Variability of Apnea-Hypopnea Index in Obstructive Sleep Apnea Using Ambulatory Polysomnography - Sforza, Emilia; Roche, Frédéric; Chapelle, Céline; Pichot, Vincent (Frontiers in Physiology, 2019)
Rationale: Patients with obstructive sleep apnea (OSA) experience respiratory events with greater frequency and severity while in the supine sleeping position. Postural preference (associated with the sleep monitoring device) and “first night effect” could explain a night-to-night variability in OSA severity. Objectives: We evaluated the variability of internight polysomnography (PSG) in a large group of OSA patients and we explored factors explaining this variability. Methods: 188 patients referred for probable OSA (aged 54.9±11.8 y) underwent two consecutive nights of at-home PSG. The effect of age, gender, obesity, neck circumference, sleep position and sleep parameters were considered to explain changes in respiratory parameters. Main Results: The mean apnea-hypopnea index (AHI) and oxygen desaturation index (ODI) were respectively 36.3±27.5 and 22.0±22.7 in the first night, with a tendency to decrease during the second night. While in mild cases (5≤AHI<15) there was a significant increase in AHI related to an increase in dorsal position time during the second night, there were no changes in moderate cases (15≤AHI<30); and in severe cases (AHI≥30) there was a significant decrease in both AHI and ODI during the second night independent of sleep position. Conclusions: The internight variability in AHI and ODI was related to changes in sleep structure with a contribution of indices of sleep fragmentation and dorsal position. Since the changes were greater in mild OSA cases, a second night could be routinely proposed in cases with relevant clinical uncertainty.